Evaluation of the aggregates used in the metropolitan region of Salvador regarding the occurrence of alkali-aggregate reactions (AAR) - Ribeiro, Daniel Veras; Oliveira Rey, Rafaela (Revista ALCONPAT, 2019)
In the present work the AAR of the aggregates used in the metropolitan region of Salvador and the use of mineral additions in order to mitigate this reaction was evaluated. The accelerated test method using mortar bars, recommended by NBR 15577-4: 2008, was used. The results indicate that the sands of the metropolitan area of Salvador have low reactivity, however, the gravels presented high reactivity and that mineral additions with pozzolanic characteristics can mitigate the AAR. This study, although limited to the conditions used, is unprecedented in the State of Bahia and presents a high index of originality, since it uses higher contents of mineral additions than conventional use. It was concluded that microsilica, if used at very high contents, can even accelerate the AAR.